Indolent infections in patients with hematologic malignancy: A single-center experience screening for tuberculosis and strongyloidiasis prior to cytotoxic therapy in Boston - K.A. Reifler; T. Francoeur Smith; G. Bodanapu; M. Fagan; D.L. Bourque; J.M. Sloan (Leukemia Research Reports)
Individuals with hematologic malignancy have increased risk of latent tuberculosis infection (LTBI) reactivation and Strongyloides stercoralis (SS) dissemination. However, screening prior to chemotherapy or corticosteroids is not routine. We conducted a LTBI and SS screening intervention amongst patients with hematologic malignancies. Over one-third immigrated from countries with high TB incidence and SS prevalence, and some had additional risk factors (HIV, HTLV-1, eosinophilia). The intervention increased screening rates but universal screening was not achieved. Screening positivity was similar pre- and post-intervention. We demonstrate a population with increased indolent infection reactivation risk. Specific infectious screening guidelines are needed to prevent significant morbidity.